FINDING OUT THE AUTHENTICITY OF THE FITRAH OF ISLAM TOWARD THE M. QURAISH SHIHABâS THOUGHT - Abidin, Ahmad Zainal (EpistemÃƒÂ©: Jurnal Pengembangan Ilmu Keislaman, 2018)
There are several primary questions which can lead to asking about the religious urgency related to the mankindâs life. âIs it available for a man to escape from the existence of religion?â âWhy does a man need a religion? Why should Islam be born as a religion?â These questions are answered by M. Quraish Shihab based on his commentary. He stated that to have a belief for a man is a nature. While the reason that brings Islam as a fitrah religion is, it is a belief which was brought by the last prophet: Muhammad (PBUH). The focus of this research is âhow is the authenticity of the Islamic concept as the fitrah religion according to M. Quraish Shihab?â This study aimed to analyze the perspective of M. Quraish Shihab as a fitrah religion based on the Qurâan, which points out to take any information about the authenticity of the concept of Islam as a fitrah religion. This research implements library research which applied hermeneutics method. The theory of Fazlur Rahman is used here, which strengthens to the double movement theory on tracking either the authenticity of the message or moral ideal as what outlined in Tafsir Al-Mishbah. Based on the research, it is concluded that the authentic meaning of the concept of Islam as a fitrah religion according to the Quraish Shihab is an exclusive belief and a positive behavior. All prophets are Muslims, but all humans alive after Prophet Muhammad should embrace Islam as part of their submission form to Allah by voluntary and peaceful ways. Non-Muslims should be persuasivelyÂ introduced to Islam. Because do not embrace Islam not only ignoring fitrah but also denying Muhammad as the last prophet. Nevertheless, M. Quraish Shihab considers itâs important for Muslims to respect other religions in order to maintain social justice by living in peace, mutual understanding and cooperation without sacrificing their faith.